A Critical Investigation of Fear Appeals in Political Discourse: A Corpus-based Linguistic Analysis of US Presidential Speeches - Tuba Latif; Aniqa Rashid; Nimra Noor; Huda Noor (University of Chitral Journal of Linguistics and Literature, 2024)
This study critically examines the use of fear appeals in US presidential speeches through a corpus-based linguistic analysis, focusing on key addresses delivered by Franklin D. Roosevelt, George W. Bush, Barack Obama, Donald Trump, and Joe Biden. The analysis explores the linguistic features and rhetorical strategies, such as evaluative language, repetition, and emotional framing, used to construct fear-based narratives during national crises. By applying Appraisal Theory, Persuasive Rhetoric, and Aristotelian Rhetoric, the research highlights the interplay between emotional engagement, credibility, and logical reasoning in shaping public opinion and mobilizing political action. The study uncovers common patterns of fear appeal usage across different presidencies, demonstrating how these leaders manipulate cognitive biases and use rhetoric to influence political decision-making. Future research will extend this analysis to explore the long-term effects of fear appeals on political engagement and public trust, offering valuable insights into the role of emotion in political discourse.